Reduced portal vein blood flow velocity in acute fatty liver of pregnancy - Zhao, Yang; Zhang, Er-ke; Li, Dan-Hua; Zhou, Yu-Jing; Jiang, Hui; Jia, Xiao-Chao; Qin, Chuan (Frontiers in Medicine, 2024)
PurposeAcute fatty liver of pregnancy (AFLP) is a severe complication that can occur in the third trimester or immediately postpartum, characterized by rapid hepatic failure. This study aims to explore the changes in portal vein blood flow velocity and liver function during pregnancy, which may assist in the early diagnosis and management of AFLP.MethodsThis longitudinal study was conducted at a tertiary healthcare center with participants recruited from routine antenatal check-ups. The study included healthy women aged 20–40 years with singleton pregnancies. Doppler ultrasonography was used to assess portal vein flow and velocity, complemented by standard laboratory tests to monitor liver function. A nomogram model integrating the clinical features and Doppler ultrasonography parameters was constructed using logistic regression analysis for differentiating AFLP from normal controls.ResultsA total of 135 women were enrolled, divided into control and AFLP groups. The AFLP group demonstrated a significant reduction in portal vein flow velocity and alterations in liver dimensions. Laboratory tests indicated elevated liver enzymes and altered lipid profiles in the AFLP group. Statistical analysis showed that portal vein flow velocity could be a sensitive marker for predicting liver dysfunction in AFLP. The area under the receiver operating characteristic (ROC) curves (AUC) of the nomogram model were 0.88 (95% confidence interval [CI]: 0.82–0.95) with specificity, sensitivity, negative predictive value, and positive predictive value of 67.8, 95.0, 95.0, and 67.8, respectively, in the training cohort and 0.86 (95% CI: 0.72–0.98) and 86.9, 75.0, 83.3, and 80.0 in the test cohort, respectively. The calibration curves demonstrated good agreement between the predicted and observed probability for predicting AFLP.ConclusionThe study underscores the potential of using portal vein flow velocity as an early diagnostic marker for AFLP in pregnant women. Further research is required to establish standardized diagnostic thresholds for portal vein flow measurements.